Analisis Pengaruh Lingkungan Kerja, Fleksibilitas Kerja, Dan Pengembangan Karir Terhadap Preferensi Karir Generasi Z - Zebua, Thessania Sherry Ariani; Pasaribu, Lamhot Henry (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of Work Environment, Job Flexibility, and Career Development on Generation Z Career Preferences. Generation Z as the new workforce has unique characteristics in determining career choices, so it is important for organizations to understand the factors that influence their preferences. This research uses a quantitative approach with a survey method through distributing questionnaires to alumni of X college. The data analysis technique used is multiple linear regression to test the effect of each independent variable on the dependent variable. The results showed that Work Environment, Work Flexibility, and Career Development have a positive and significant effect on Generation Z Career Preferences. These findings confirm the importance of organizations creating a conducive, flexible work environment and providing career development opportunities to attract and retain Generation Z talent.